2017
DOI: 10.1002/jgm.2998
|View full text |Cite
|
Sign up to set email alerts
|

Co‐delivery of hypoxia inducible factor‐1α small interfering RNA and 5‐fluorouracil to overcome drug resistance in gastric cancer SGC‐7901 cells

Abstract: Co-delivery of siRNA and 5-fluorouracil chitosan nanoparticles is an attractive strategy for overcoming multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…It was reported that hypoxia confers sorafenib resistance in myeloid leukemia, renal, or gastric cancer cells 35 38 and is responsible for the acquired resistance to different anticancer drugs in HCC cells, including doxorubicin, etoposide, cisplatin, SN38, and 5-fluorouracil 39 43 . In fact, Liang et al 32 reported that the continued administration of sorafenib in HCC subcutaneous mouse tumor models increases the protein levels and transcriptional activity of HIF-1α.…”
Section: Hifs and Sorafenib Resistancementioning
confidence: 99%
“…It was reported that hypoxia confers sorafenib resistance in myeloid leukemia, renal, or gastric cancer cells 35 38 and is responsible for the acquired resistance to different anticancer drugs in HCC cells, including doxorubicin, etoposide, cisplatin, SN38, and 5-fluorouracil 39 43 . In fact, Liang et al 32 reported that the continued administration of sorafenib in HCC subcutaneous mouse tumor models increases the protein levels and transcriptional activity of HIF-1α.…”
Section: Hifs and Sorafenib Resistancementioning
confidence: 99%
“…It has also been observed that the synergistic cytotoxic potential for Chk1 inhibition during 5‑FU treatment in p53‑deficient colon cancer cells with or without 5‑FU resistance. 116 , 117 …”
Section: Different Aspects Of the Use Of Nanocarriers – Prevention Diagnostic And Therapeutic Applicationmentioning
confidence: 99%
“…It has also been observed that the synergistic cytotoxic potential for Chk1 inhibition during 5-FU treatment in p53-deficient colon cancer cells with or without 5-FU resistance. 116,117 Paclitaxel (PTX) is used against many forms of cancer, for example, ovarian, breast, lung, Kaposi sarcoma, cervical, and pancreatic cancer. Mechanism of action relates to targeting microtubules -it disrupts the major function of microtubules, which is the production of the mitotic spindle during cell division, as well as maintenance of the cell structure, motility, and cytoplasmic movement within the cell.…”
Section: The Efficiency Of Encapsulation/ Immobilization Of Drugs In Carriersmentioning
confidence: 99%
“…Hypoxia contribution to chemoresistance development in HCC has been described after the administration of drugs, such as 5-fluorouracil (5-FU) [25], doxorubicin, and cisplatin [26]. Involvement of hypoxic environment in the acquired resistance to sorafenib has also been reported in renal cancer [27,28], gastric cancer [29], and acute myeloid leukaemia [30]. In samples of patients with untreated HCC sensitive and resistant to sorafenib, intratumoral hypoxia increased in patients resistant to sorafenib as opposed to sensitive ones [20].…”
Section: Discussionmentioning
confidence: 99%